Laporan Kasus : Bayi 3 Bulan dengan Ulkus Kornea Ocular Dextra et causa Koloboma Palpebra Superior Ocular Dextra - Rani Himayani; Farhandika Muhammad (Medula, 2021)
Coloboma is a condition of congenital malformation in which the ocular structures are not fully formed due to failed fusion of the optic fissure during the embryonic development. The resulting defects can affect different structures, such as the eyelids, iris, lens, ciliary body, choroid, optic nerve, and retina.Eyelid coloboma is a congenital disorder that can occur unilateral or bilateral, partially or completely. This is due to the failure of mesodermal fusion during eyelid embryogenesis. There is no fusion between contigous tissue, the failure of the mesenchyme to fill the embryogenic process, and the result of necrosis due to the suppression effect of the amniotic band syndrome. This case reports a 3 month old baby with a chief complaint of white part  on right eye since 15 days. The complaint was initiated with the patient being born without a complete right eyelid. The ophthalmology examination of the right eye found that the sharp vision of the baby began to be able to follow the moving object that was seen, but the baby did not follow the instructions to see from one object to another without having to move his head, the pupil diameter was the same in both eyes, with normal pupillary reflex. Eyelid inspection found a coloboma on the right upper eyelid. In the sclera and limbus, there was minimal ciliary injection, the cornea was cloudy, the front chamber was shallow and it looked positive.Based on the history, physical examination, and investigations, the patient was diagnosed as right ocular corneal ulcer et causa coloboma of the superior ocular palpebrae. Medical management by administering antibiotic therapy and artificial tears, and in the patient planned operative action in the form of reconstruction of the superior palpebra on the oculi dextra.